2016
DOI: 10.3109/07435800.2015.1135444
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and hypercholesterolemia in patients with prolactinomas: Could DHEA-S and growth hormone be the missing link?

Abstract: DHEA-S, GH and prolactin remained significant even after adjustment for BMI. GH and IGF-I were associated with BMI and LDL cholesterol, but the association diminished after adjustment for serum prolactin.Conclusions: Prevalence of obesity is four times higher in patients with prolactinomas than in patients with nonfunctional adenomas. Higher DHEA-S and lower GH levels in patients with prolactinomas may have an important role in prolactin-induced metabolic effects. Further studies are needed.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…In a study in which non-functional pituitary adenomas and prolactinoma were evaluated, BMI was reported to be significantly higher in the prolactinoma group. That group also had diminished growth hormone and insulin-like growth factor-1 levels (22). It has been shown that the modulatory effect of PRL may influence fat tissue and PRL changes body weight and composition.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which non-functional pituitary adenomas and prolactinoma were evaluated, BMI was reported to be significantly higher in the prolactinoma group. That group also had diminished growth hormone and insulin-like growth factor-1 levels (22). It has been shown that the modulatory effect of PRL may influence fat tissue and PRL changes body weight and composition.…”
Section: Discussionmentioning
confidence: 99%
“…What's more glyburide increased PRL secretion from anterior pituitary through inhibition of somatostatin (endogenous inhibitor of prolactin). [33]…”
Section: Discussionmentioning
confidence: 99%
“…The dyslipidaemia, glucose intolerance, hyperinsulinaemia and insulin resistance described in these situations have been improved in some cases by lowering prolactin levels with dopamine agonist drugs. 23,25,32,33,35,36,43,44 Metabolic pathological aspects of prolactin excess in humans are also exemplified by the association between the PRL locus BAT, probably related to increased NPY levels in the DMH 95 as a result of the known regulation of BAT activity in this brain region. 114…”
Section: Prol Ac Tin and Ad Ip Os E Tissuementioning
confidence: 99%
“…28 Pathological hyperprolactinaemia resulting from pituitary tumours or chronic blockade of dopamine receptors during psychiatric medication has been associated with metabolic alterations. In patients with prolactinomas, predisposition to obesity, 23,25,[30][31][32][33][34] dyslipidaemia, [35][36][37] high cholesterol levels, 33 non-alcoholic fatty liver disease (NAFLD), 34 metabolic syndrome, 38 hyperinsulinaemia, [37][38][39] insulin resistance 35,[39][40][41] and intolerance to glucose have been described. Notably, not all metabolic manifestations are present in every cohort of patients, revealing a selective predisposition of patients to different aspects of metabolic disturbances associated with prolactin.…”
mentioning
confidence: 99%